PENGUJIAN KETAHANAAN GALUR HASIL PERSILANGAN PADI GOGO LOKAL BENGKULU PADA KONDISI KEKURANGAN AIR - Asfaruddin Asfaruddin; Sri Mulatsih (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2016)
Dry season which often come is quicker, becoming one of the constrictor factor produce of upland rice. Existence of lacking of water cause crop experience of stres so that unable to grow and productive maximally. One of the effort to overcome degradation result of effect of lacking of water is assemble pre-eminent upland rice varietas tolerance to lacking of water. This research is conducted to evaluated the tolerance of genotipes result crossing of Bengkulu local varieties upland rice to dryness grasp. Research conducted year dry season 2015, using split plot design. Result of research indicate that Genotipa result of crossing of local upland rice of Bengkulu have difference of its resilience to dryness grasp. Lenient Genotipa of dryness at attempt of green house is 31,25 %, that is UNHZ 1, UNHZ 6, UNHZ 14, UNHZ 15A, UNHZ 16, UNHZ 23, UNHZ 24, UNHZ 26, UNHZ 27 And UNHZ 31. Lenient Geotipa to dryness grasp at attempt of field is 19,23 %, that is UNHZ 14A, UNHZ 14B, UNHZ 21, UNHZ 22, UNHZ 23, UHZ 24, UNHZ 26, UNHZ 27, UNHZ 31, UHNZ 32, UNHZ 56, UNHZ 58, UNHZ 61, UNHZ 62, UNHZ 66, UNHZ 67, UNHZ 91, UNHZ 93, UNHZ 96 and UNHZ 97. Genotipa showing symptom hold up goodness at research of green house and also research of field is UNHZ1, UNHZ 14A, UNHZ 15 A , UNHZ 23, UNHZ 24, UNHZ 26, UNHZ 27 and UNHZ 31. Keywords: uapland rice, dryness grasp, tolerance.